Organizational and pedagogical conditions of influence of the objective and methods competence of teachers of Social Science disciplines on the formation of social science skills of students - Старєва, А. М. (Pedagogy of Higher and Secondary Education, 2013)
Starуeva А. М. Organizational and pedagogical conditions of influence of the objective and methods competence of teachers of Social Science disciplines on the formation of social science skills of students. The author analyzes the competence-based approach to the learning process according to new state educational standards (on the example of educational field «Social Science»), defines organizational and pedagogical conditions of influence of the objective and methods competence of teachers of Social Science disciplines on the formation of social science skills of students.